Ethiopia Alive & Thrive Endline Survey 2014: Community - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the community survey that was conducted to gather data at endline as a part of the impact evaluation of the Alive & Thrive (A&T) interventions in Ethiopia. The broad objective of the impact evaluation in Ethiopia is to measure the impact of A&T’s community-based interventions, delivered through the government's health extension program (HEP) platform, in the reduction of stunting and improvement of IYCF practices in two regions where the IFHP operates, namely Tigray and SNNPR (Southern Nations, Nationalities, and People’s Region). A&T is a six-year initiative to facilitate change for improved infant and young child feeding (IYCF) practices at scale in Bangladesh, Ethiopia, and Viet Nam. The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing stunting of children 0-24 months of age. The impact evaluation of A&T’s community-based intervention and mass media activities applied an “adequacy design,” which involves pre- and post-intervention assessments without a non-intervention comparison group. A total of 75 enumeration areas (EAs) were randomly selected from woredas (districts) that were part of the IFHP platform for A&T in Tigray and SNNPR. Repeated cross-sectional surveys were conducted at baseline (2010) and endline (2014) in the 75 EAs. A short questionnaire was administered to community leaders to gather information on the contextual factors at the community level as well as to understand differences in characteristics across the clusters (EA) over time. One questionnaire was completed for each cluster (EA). This information at the community level is critical to control for externalities that could influence the outcome of the program. The Ethiopia endline community questionnaire provided information on the following: 1) General characteristics of the EA/kebele (population, livelihood, season of food shortage), 2) Infrastructure (access to main road, electricity, access to clean water, 3) Distance from the nearest major town, type of transportation use to reach the town, 4) Access to the nearest market, 5) Migration patterns, 6) Social and food assistance (productive safety net program, community-based nutrition program), 7) Natural disasters occurred in the area during the last year, 8) Availability and access to health and education facilities (health post, government hospital, private clinic, junior and high school, college).